Peran Kepolisian Daerah Sumatera Selatan Dalam Mencegah Tindak Pelecehan Seksual Pada Anak Kota Palembang (Studi Ditreskrimum Subdit IV Polda Sumsel) - Juliani, Lia (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This thesis is entitled "The Role of the South Sumatra Police in Preventing Sexual Harassment of Children in the City of Palembang (Study of Ditreskrimum Subdit IV Polda Sumsel)" which aims to determine the role played by Ditreskrimum Subdit IV and find out what factors cause acts of sexual abuse against children. in Palembang City. The type of research carried out is qualitative research. The data collection methods used in this research are observation, interviews and documentation. The interview used was a structured interview, so that the author examined the problems raised based on the title of the informant which was carried out on (25 September 2023 to 20 October 2023). The theory used in this research is the role theory put forward by Prof. Dr. Soerjono Soekanto (1982). The results of the research show the role of the South Sumatra Regional Police's Subdit IV Ditreskrimum, especially regarding the factors that cause acts of sexual abuse against children to occur in Palembang City. The role carried out by the Ditreskrimum Subdit IV Polda South Sumatra is to carry out preventive non-penal efforts in the form of (prevention, deterrence or control) before a crime occurs. Forms of prevention taken include data collection, monitoring and supervision as well as outreach and education.